Pengaruh Harga, Promosi, Dan Kualitas Produk Indomie Terhadap Keputusan Pembelian Di Warmindo Jayaberkah - Sabila Imelda Putri; Salsa Ainurrohmah; Slamet Bambang Riono; Muhammad Syaifulloh (CiDEA Journal, 2023)
Indomie continues to adapt to consumer trends and preferences by launching product variants that suit local tastes or follow specific food trends helping Indomie stay relevant in the market. This study aims to analyze the influence of price, quality, and quantity on purchasing decisions in terms of Indomie instant noodle products. Price, promotion, and product quality were identified as independent variables in this study with purchasing decision as the dependent variable. The study was conducted with quantitative methodology. The population in this study was randomly taken from 430 Warmindo Jayaberkah consumers. The number of samples in this study was 25% of the total population obtained by 107 respondents. The results showed that price and product promotion did not affect purchasing decisions, while product quality influenced purchasing decisions. Product price, promotion, and product quality together influence purchasing decisions. Product pricing, promotion, and product quality influence purchasing decisions by 63.2%. The study's findings would suggest that product quality variables have a substantial impact on purchasing decisions.